Trpc2-deficient lactating mice exhibit altered brain and behavioral responses to bedding stimuli - Hasen, Nina S. (2010)
The trpc2 gene encodes an ion channel involved in pheromonal detection and is found in the vomeronasal organ. In tprc2(-/-) knockout (KO) mice, maternal aggression (offspring protection) is impaired and brain Fos expression in females in response to a male are reduced. Here we examine in lactating wild-type (WT) and KO mice behavioral and brain responses to different olfactory/pheromonal cues. Consistent with previous studies, KO dams exhibited decreased maternal aggression and nest building, but we also identified deficits in nighttime nursing and increases in pup weight. When exposed to the bedding tests, WT dams typically ignored clean bedding, but buried male-soiled bedding from unfamiliar males. In contrast, KO dams buried both clean and soiled bedding. Differences in brain Fos expression were found between WT and KO mice in response to either no bedding, clean bedding, or soiled bedding. In the accessory olfactory bulb, a site of pheromonal signal processing, KO mice showed suppressed Fos activation in the anterior mitral layer relative to WT mice in response to clean and soiled bedding. However, in the medial and basolateral amygdala, KO mice showed a robust Fos response to bedding, suggesting that regions of the amygdala canonically associated with pheromonal sensing can be active in the brains of KO mice, despite compromised signaling from the vomeronasal organ. Together, these results provide further insights into the complex ways by which pheromonal signaling regulates the brain and behavior of the maternal female.